Analisis Kinerja Keuangan pada PT. Indo-Rama Synthetics TBK - Nilasari Resky Pala’langan; Dina Ramba (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This research purposed to analyze the financial performance of PT. Indo-Rama Synthetics Tbk. The research was conducted using a quantitative approach with financial reports as a data source to examine financial performance based on profitability ratios, liquidity ratios, activity ratios and solvency ratios. The research examines financial performance starting from 2020 to 2022 with financial reports obtained from the official website of the Indonesia Stock Exchange (BEI). Based on the results of the analysis, it was found that in the profitability assessment only the return on assets ratio had reached the efficient criteria, while the net profit margin and return on equity ratios were considered inefficient. In assessing liquidity, the current ratio and quick ratio are not yet liquid. Activity assessment through inventory ratios, fixed asset turnover and total asset turnover is considered to have not met the efficient level each year. Meanwhile, in the solvency assessment, it was found that the overall ratios used, namely the debt to asset ratio and the debt to equity ratio, met good criteria.